Festive Culture of Kryashens - Khusnutdinova, Ksenia Yu.; Titova, Tatyana A.; Frolova, Elena V. (Journal of History Culture and Art Research, 2017)
Traditional festive ritual culture occupies an important position in the life of the Kryashens. The article is based on our own field research conducted in 2014. The purpose of the article is to study traditional holidays and their significance for the Kryashens. The article showed popular traditional Kryashen holidays, their innovations and origins, which go deep into history and are closely intertwined with the culture of neighboring peoples. The methodological base of the study assumes the consideration and the analysis of the traditional festive culture of the Kryashens. The work uses general historical methods: historical-comparative, cultural-anthropological, the method of complex analysis and the discriminative method. The work is also based on the combination of quantitative and qualitative methods: discourse - mass survey through questionnaires, in-depth interviews, focus groups, included monitoring. The article gives a detailed description of each holiday. Kryashen people keep the ancient traditions of their ancestors, combining their Turkic roots and Orthodox culture. During the long parallel development of national holidays, customs and religions, Christianity has become an integral part of the Kryashen spiritual life - this confirms the special significance of Orthodox religious holidays. Also, ethnic-cultural characteristics and the celebration of traditional holidays are of great importance for Kryashens. Particularly honored calendar holidays for the Kryashens are the following ones: Easter, Christmas, Epiphany, Petrov Day (Pitrau), Trinity, Nardugan, Semik, Pokrov. These festive traditions are marked by a certain important value and stability in the cultural environment of the Tatarstan Kryashens. The materials of the article can be useful for ethnologists, social and cultural anthropologists, and everyone interested in this topic.